A Convenient Palladium‐Catalyzed Carbonylative Synthesis of 2‐Aminbenzoxazinones from 2‐Bromoanilines and Isocyanates. Issue 20 (20th March 2013) - Wu, Xiao‐Feng; Sharif, Muhammad; Shoaib, Khurram; Neumann, Helfried; Pews‐Davtyan, Anahit; Langer, Peter; Beller, Matthias
<x xml:space="preserve">Abstract</x> Mon ami(ne)! A general and convenient methodology for 2‐aminobenzoxazinone synthesis has been developed (see scheme). Readily available 2‐bromoanilines and isocyanates were used as substrates and various products have been prepared in good yields. Notably, [Mo(CO)6] as a solid CO source was applied instead of gas.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>